Yoga in the Management of Chronic Disease: A Systematic Review and Meta-analysis. Issue 7 (July 2015) - Desveaux, Laura; Lee, Annemarie; Goldstein, Roger; Brooks, Dina
Abstract : Background: Heart disease, stroke, and chronic obstructive pulmonary disease (COPD) are the leading causes of death and disability worldwide. Although individuals with these conditions have been reported to benefit from yoga, its effectiveness remains unclear. Objective: To perform a systematic review of the effectiveness of yoga on exercise capacity, health related quality of life (HRQL), and psychological well-being for individuals with chronic disease and describe the structure and delivery of programs. Research Design: We performed a systematic review of randomized controlled trials examining yoga programs for individuals with heart disease, stroke, and COPD compared with usual care. Quality was assessed using the Cochrane risk of bias tool. Meta-analyses were conducted using Review Manager 5.3. The protocol was registered on PROSPERO (CRD42014014589). Results: Ten studies (431 individuals, mean age 56±8 y) were included and were comparable in their design and components, irrespective of the chronic disease. The standardized mean difference for the mean change in exercise capacity was 2.69 (95% confidence interval, 1.39–3.99) and for HRQL it was 1.24 (95% confidence interval, −0.37 to 2.85). Symptoms of anxiety were reduced after yoga in individuals with stroke, although this was not observed in individuals with COPD. The effect of yoga on symptoms of depression varied across studies with no significant effects compared with usual care. Conclusions: Yoga programs have similar designs and components across chronic disease populations. Compared with usual care, yoga resulted in significant improvements in exercise capacity and a mean improvement in HRQL. Yoga programs may be a useful adjunct to formal rehabilitation programs.